Impact of delivery mode-associated gut microbiota dynamics on health in the first year of life - Marta Reyman (Nature Portfolio, 2019)
Here, in a cohort of infants unexposed to maternal antibiotics, the authors analyse the gut microbiome development of children born naturally and by caesarean section, finding a higher abundance of known pathogens in the latter group, and an association between these bacteria and a higher incidence of respiratory infections in the first year of life.